Allergen immunotherapy combined with Notch pathway inhibitors improves HDM-induced allergic airway inflammation and inhibits ILC2 activation - Tong, Yu; Wang, Lei; Wang, Lingya; Song, Jingjing; Fan, Junwen; Lai, Chuqiao; Bao, Jiali; Weng, Cuiye; Wang, Yufei; Shuai, Jilong; Zhang, Hui; Zhang, Weixi (Frontiers in Immunology, 2024)
Group 2 innate lymphoid cells (ILC2s) perform an important role in house dust mite (HDM)-induced allergic inflammation, and allergen immunotherapy (AIT) has the potential to treat the disease by reducing the frequency of ILC2s. Despite the tremendous progress of AIT in the therapy of allergic diseases, the degree of control of allergic symptoms still needs to be improved. Previously, our group revealed that Notch signaling pathway inhibitors can reduce allergic airway inflammation in mice. Notch signaling induces lineage plasticity of mature ILC2. Here, we demonstrated that AIT alleviates allergic airway inflammation and suppresses the frequency of ILC2s induced by HDM. Interestingly, AIT combined with a γ-secretase inhibitor (GSI), an inhibitor of the Notch signaling pathway, was found to significantly inhibit the frequency of ILC2s, reduce airway inflammation and suppress Th2-type responses in a mouse model. Lung ILC2s from HDM challenged mice with or without AIT were also treated with GSI in vitro. And we found that GSI can dramatically reduced secretion of type 2 inflammatory factors in ILC2s. These findings suggest that Notch signaling pathway inhibitors can be used as adjuvant therapy for AIT and may have potential treatment value in the cooperative control of allergic airway inflammation during early AIT.